Answer:
The correct answer is:
(7s-2)+3+(s+3) = 52, or 8s+4 = 52.
Step-by-step explanation:
Since s is the son's age, "two less than seven times" the son's age would be represented by 7s-2. To represent this in 3 years, we would add 3: (7s-2)+3. In 3 years, the son's age, s, would be represented by s+3. We are told that the sum of these ages will be 52; this gives us (7s-2)+3+(s+3) = 52.
To simplify this, combine like terms. 7s+s = 8s; -2+3+3 = 4. This gives us 8s+4=52.
Answer:
Let x rep the lenght of the shorter one
Then the longer one is 2x+1
Therefore
(2x+1) + x = 16
We now solve for x
2x + 1 + x = 16
Group and evaluate like terms
3x +1 = 16
3x = 16 -1
× = 15/3
x = 5
So the shorter one is 5 ft
The longer one is 2(5)+1= 11
Answer:
-2x
Step-by-step explanation:
4x-6x=-2x. You need to combine like terms or subtract 6 from 4 which is -2 the you add then put the x back in
<u>To prove the trigonometric equation:</u>
![\sin ^{3} x+\cos ^{3} x=(\sin x+\cos x)(1-\sin x \cos x)](https://tex.z-dn.net/?f=%5Csin%20%5E%7B3%7D%20x%2B%5Ccos%20%5E%7B3%7D%20x%3D%28%5Csin%20x%2B%5Ccos%20x%29%281-%5Csin%20x%20%5Ccos%20x%29)
![RHS=(\sin x+\cos x)(1-\sin x \cos x)](https://tex.z-dn.net/?f=RHS%3D%28%5Csin%20x%2B%5Ccos%20x%29%281-%5Csin%20x%20%5Ccos%20x%29)
We know that
, substitute this in place of 1.
![=(\sin x+\cos x)(\sin^2x +\cos^2x-\sin x \cos x)](https://tex.z-dn.net/?f=%3D%28%5Csin%20x%2B%5Ccos%20x%29%28%5Csin%5E2x%20%2B%5Ccos%5E2x-%5Csin%20x%20%5Ccos%20x%29)
Multiply each term of the first term with each term of the 2nd term.
![=\sin^3x + \sin x \cos^2x-\sin^2 x \cos x+\cos x \sin^2 x + \cos^3 x-\sin x\cos^2 x](https://tex.z-dn.net/?f=%3D%5Csin%5E3x%20%2B%20%5Csin%20x%20%5Ccos%5E2x-%5Csin%5E2%20x%20%5Ccos%20x%2B%5Ccos%20x%20%5Csin%5E2%20x%20%2B%20%5Ccos%5E3%20x-%5Csin%20x%5Ccos%5E2%20x)
Group like terms together.
![=\sin^3x +( \sin x \cos^2x-\sin x\cos^2 x)+(\cos x \sin^2 x-\sin^2 x \cos x) + \cos^3 x](https://tex.z-dn.net/?f=%3D%5Csin%5E3x%20%2B%28%20%5Csin%20x%20%5Ccos%5E2x-%5Csin%20x%5Ccos%5E2%20x%29%2B%28%5Ccos%20x%20%5Csin%5E2%20x-%5Csin%5E2%20x%20%5Ccos%20x%29%20%2B%20%5Ccos%5E3%20x)
![=\sin^3x +( 0)+(0) + \cos^3 x](https://tex.z-dn.net/?f=%3D%5Csin%5E3x%20%2B%28%200%29%2B%280%29%20%2B%20%5Ccos%5E3%20x)
![=\sin^3x + \cos^3 x](https://tex.z-dn.net/?f=%3D%5Csin%5E3x%20%2B%20%5Ccos%5E3%20x)
= LHS
RHS = LHS
![\sin ^{3} x+\cos ^{3} x=(\sin x+\cos x)(1-\sin x \cos x)](https://tex.z-dn.net/?f=%5Csin%20%5E%7B3%7D%20x%2B%5Ccos%20%5E%7B3%7D%20x%3D%28%5Csin%20x%2B%5Ccos%20x%29%281-%5Csin%20x%20%5Ccos%20x%29)
Hence proved.
so we know she has sculptures and paintings, if she sold twice as many paintings as sculptures, that means that for every 2 paintings, she sold 1 sculpture, so the paintings and sculptures are on a 2:1 ratio.
we know she sold a total of 57, so we'll need to split 57 in a 2:1 ratio, we'll simply divide the whole amount of 57 by (2+1) and distribute accordingly.
![\bf \cfrac{paintings}{sculptures}\qquad 2:1\qquad \cfrac{2}{1}\qquad \qquad \cfrac{2\cdot \frac{57}{2+1}}{1\cdot \frac{57}{2+1}}\implies \cfrac{2\cdot 19}{1\cdot 19}\implies \cfrac{\boxed{38}}{19}](https://tex.z-dn.net/?f=%5Cbf%20%5Ccfrac%7Bpaintings%7D%7Bsculptures%7D%5Cqquad%202%3A1%5Cqquad%20%5Ccfrac%7B2%7D%7B1%7D%5Cqquad%20%5Cqquad%20%5Ccfrac%7B2%5Ccdot%20%5Cfrac%7B57%7D%7B2%2B1%7D%7D%7B1%5Ccdot%20%5Cfrac%7B57%7D%7B2%2B1%7D%7D%5Cimplies%20%5Ccfrac%7B2%5Ccdot%2019%7D%7B1%5Ccdot%2019%7D%5Cimplies%20%5Ccfrac%7B%5Cboxed%7B38%7D%7D%7B19%7D)